Decadal Changes in Bomb-Produced Radiocarbon in the Pacific Ocean from the 1990s to 2000s - Kumamoto, Yuichiro; Murata, Akihiko; Kawano, Takeshi; Watanabe, Shuichi; Fukasawa, Masao (Radiocarbon, 2013)
In the 2000s, radiocarbon in dissolved inorganic carbon was measured during 7 revisit cruises along the lines of the World Ocean Circulation Experiment in the Pacific Ocean. Comparison of 14 C data along these lines from the 1990s and 2000s revealed decadal changes of 14 C concentration in the thermocline, most of which were due to temporal changes in the bomb-produced 14 C. Vertical profiles and vertical-integrated inventories of the bomb 14 C in the subarctic and equatorial regions did not change appreciably. In the southern subtropical region, 14 C decreased in the upper thermocline from the surface to ∼500 m depth. In contrast, 14 C increased in the lower thermocline below ∼500 m depth. The opposing directions in 14 C change resulted in small temporal changes in the total inventory of bomb 14 C. On the other hand, the water-column inventory significantly decreased in the northwestern subtropical region due to the 14 C decrease in the upper thermocline. These decadal changes in bomb 14 C indicate that the turnover time of thermocline circulation in the northwestern subtropical region is faster than that in the southern subtropical region, and imply an interbasin transport of bomb 14 C from the North Pacific to other basins.